Intratumoral gene expression of 5-fluorouracil pharmacokinetics-related enzymes in stage I and II non-small cell lung cancer patients treated with uracil-tegafur after surgery: A prospective multi-institutional study in Japan. Issue 1 (January 2015) - Eguchi, Keisuke; Oyama, Takahiko; Tajima, Atsushi; Abiko, Tomohiro; Sawafuji, Makoto; Horio, Hirotoshi; Hashizume, Toshinori; Matsutani, Noriyuki; Kato, Ryoichi; Nakayama, Mitsuo; Kawamura, Masafumi; Kobayashi, Koichi
Highlights We assessed gene expression levels of 5-FU related enzymes in stage I/II NSCLC. Tumors from 236 patients with UFT administration after surgery were examined. Thymidylate synthase gene expression was an independent predictive factor for DFS.